Potential of polyhydroxyalkanoate (PHA) polymers family as substitutes of petroleum based polymers for packaging applications and solutions brought by their composites to form barrier materials - Keskin, Gulsah; Kizil, Gulnur; Bechelany, Mikhael; Pochat-Bohatier, Celine; Oner, Mualla (WALTER DE GRUYTER GMBH, 2017)
Today, there is an increasing concern about protection of ecological systems. Petro-based synthetic polymers are not biodegradable and cause environmental pollution. These polymers that are stuck in nature, affect wildlife adversely. Also, in future petrochemical materials will drain away and demand for eco-friendly plastics which can substitute synthetic plastics will increase. Biopolymers are products which can be degraded by enzymatic activities of various microorganisms, and the degradation products are nontoxic. They are attractive alternatives to non-degradable materials in short-term applications such as packaging. Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) is a member of polyhydroxyalkanoate (PHA) family which is biodegradable and produced by microorganism. It has good gas barrier properties that make it convenient to use in different applications. The present paper gives an overview on PHAs and their composites, their main properties, with a specific focus on potential applications of PHBV in packaging.
Keywords: composite materials; materials science; nanocomposites; NICE-2016; polymers; BIODEGRADABLE POLYMERS; POLY(3-HYDROXYBUTYRATE-CO-3-HYDROXYVALERATE); FILMS; BIOCOMPOSITES; NANOBIOCOMPOSITES; PERFORMANCE; BLENDS; GAS; PERMEABILITY; Chemistry